2022
DOI: 10.4018/ijbir.297614
|View full text |Cite
|
Sign up to set email alerts
|

Facial Skincare Journey

Abstract: Consumer journey analysis led to efficient marketing implementation. A journey represents a path of steps and interaction between consumer and service units at each touchpoint. Dissatisfaction in the touchpoint, causes a negative effect to retain a customer. Previous studies always constructed the journey maps relied on the narrative approach. According to use Google, consumers always face massive websites to access, which is a pain point in the journey. Improving consumer buying, led to the research aims: ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 53 publications
(78 reference statements)
3
6
1
Order By: Relevance
“…Trust in online marketing is important because it mixes emotions and judgments that can evolve and change over time. Trust is a key factor in online business transactions because online transaction performance is subject to uncertainty and error from non-human factors, and if there is distrust, it will harm consumer satisfaction in transactions (Piriyakul et al, 2015) The results of this study strengthen the findings of the study (Piriyakul et al, 2015) ( Malhotra et al, 2017) concluded that trust has a significant positive effect on satisfaction. Research (Dwi & Raka, 2022) states that trust significantly affects customer satisfaction.…”
Section: Trust Can Increase Customer Satisfactionsupporting
confidence: 70%
See 4 more Smart Citations
“…Trust in online marketing is important because it mixes emotions and judgments that can evolve and change over time. Trust is a key factor in online business transactions because online transaction performance is subject to uncertainty and error from non-human factors, and if there is distrust, it will harm consumer satisfaction in transactions (Piriyakul et al, 2015) The results of this study strengthen the findings of the study (Piriyakul et al, 2015) ( Malhotra et al, 2017) concluded that trust has a significant positive effect on satisfaction. Research (Dwi & Raka, 2022) states that trust significantly affects customer satisfaction.…”
Section: Trust Can Increase Customer Satisfactionsupporting
confidence: 70%
“…Research (by Narahdita et al, 2020) ; (Dwi & Raka, 2022) concluded that trust significantly positively affects reuse intention. This research contrasts (with Piriyakul et al, 2015); Tun (2020) found that trust does not affect the intention to reuse. Research (Ladkoom & Thanasopon, 2020) ; (Anshori et al, 2022) concluded that trust has no effect on reuse intention.…”
Section: Figure 1 E-wallet Userscontrasting
confidence: 68%
See 3 more Smart Citations